THE EFFECT OF ISLAMIC FINANCIAL DEVELOPMENT AND HUMAN DEVELOPMENT ON INCOME INEQUALITY: DOES ISLAMIC FINANCE KUZNETS CURVE VALID IN THE OIC COUNTRIES? - Kamalu, Kabiru; Wan Ibrahim, Wan Hakimah Bint (Journal of Islamic Monetary Economics and Finance, 2023)
Income inequality is evident in all countries regardless of the level of development or income status. Islamic financial system has Shariah-compliant financial instruments that, when properly utilized, can facilitate equitable income distribution in the OIC member countries. This study examines the effect of Islamic financial development and human development on income inequality in the OIC. The study also analyzes the validity of the Islamic finance Kuznets curve hypothesis. We employ FMOLS and DOLS estimators with data from 20 OIC member countries covering the period from 2012 to 2022. The results show that Islamic financial development and human development promote equitable income distribution. The findings also confirm the validity of the Islamic finance Kuznets curve hypothesis. Thus, to reduce the income gap in the OIC, Islamic financial institutions should expand further via for examples innovation in Shariah-compliant Islamic financial products and services. In addition, policymakers should prioritize policies and programs that can promote Islamic financing and improve human development in the OIC member countries.